Goblin spiders, ghosts of flowers and butterfly fantasies: Lafcadio Hearn's transnational, transmedia and trans-species aesthetics of the weird. Issue 2 (2nd April 2020) - Manning, Paul
Abstract: This article approaches the writings of Lafcadio Hearn, an exotic, wandering, homeless 'ghost of no place' (Nabae 2014 ), born in Greece, raised in Ireland, who became a fiction writer famous for turning both New Orleans and Japan into weird, haunted, literary landscapes. Hearn always insisted his writings should be examined in their own terms as a transnational, transmedia and trans-species aesthetics of 'weird' contact between worlds. There are three kinds of contact between worlds: transnational, a traffic in spirits across spaces in an orientalist imaginative geography; transmedia, as the monstrous qualities of ghosts, goblins and fairies bleed into and across media forms; and trans-species, as monstrous qualities moves across species, between humans, goblins and insects. The forms of representation of monsters take on the properties of the monsters they are most associated with, ghostly photographs and colorful fairylands, that I will call monstrous media. At the same time, this transnational and transmedia aesthetics of the weird moves from images on Japanese fans to the wings of insects, from Japanese cemeteries to insect ecologies and Buddhist cosmologies in which humans are reborn as goblins, insects, or hybrid goblin-insects.